Analisis Laju Perubahan Garis Pantai Pulau Karimun Besar Menggunakan DSAS (Digital Shoreline Analysis System) - Dian Kharisma Dewi; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Shoreline changes could occurred because of hydrodinamically nature in coastal zone. The purpose of this study is to identify and approximating rate of shoreline changes which occurred in Karimun Besar Island. This study used to analyzed shoreline changesbased on remote sensing (satellite) data that processed by GIS (Geographic Information System). Then, to analyze the rate of its shoreline changes using DSAS (Digital ShorelineAnalysis System) with LRR (Linear Regression Rate) statistic method. The result found that shoreline has changes through 25 years (1991-2016) that abrasions are 1,63m/y and accretions are 3,78m/y.Keywords : Shoreline Changes, Satellite Data, DSAS